Crystal Structure, Infrared Spectra, and Microwave Dielectric Properties of Ce2(Zr0.94Sn0.06)3(MoO4)9 Ceramics With Low Sintering Temperature - Tian, Huanrong; Liu, Xin; Yang, Yaokang; Wu, Haitao; Zhang, Zhiliang (Frontiers in Materials, 2020)
Ce2(Zr0.94Sn0.06)3(MoO4)9 (CZSM) ceramics were synthesized via a traditional solid-state method to improve Q·f value. The effects of Sn-substitution on phase composition, density, microstructure and dielectric properties as a function of sintering temperature were discussed. It was clear that XRD analysis revealed a trigonal structure formed in all sintering temperature ranges. Dense and homogeneous microstructure can be obtained in samples sintered at 750-850 °C. The complex permittivity values were obtained from infrared reflectivity spectra. The dielectric permittivity and loss were 10.92 and 3.36×10-3, respectively, which agreed well with the measured values. The complex chemical bonds of CZSM ceramics were calculated based on P-V-L theory, which can be used to analyze the relationship between material structure and dielectric properties. The optimal microwave dielectric properties of εr=10.4, quality factor Q·f=59,660 GHz (at 9.70 GHz), and τf=-7.52 ppm/°C were achieved in CZSM ceramics sintered at 800 °C.